Epidemiological Profile of Unintentional Childhood Injuries in Urban Area of Mangaluru Taluk, Dakshina Kannada District, Karnataka State, India - Abhay S Nirgude; Mubeena Haleema (Medsci Publications, 2024)
Introduction: Worldwide injury & violence is most important cause of death in children, every year it causes death in approximately 950000 children under the age group of 18. This study was conducted to find out the magnitude & epidemiological factors associated with unintentional childhood injuries. Methods: The study was conducted in urban field practice area of a Medical College, in Southern India. Community based cross sectional study was conducted by enrolling 500 children (0-18 years) during October 2018 to September 2020. Multistage simple random sampling method was followed to select the participants. Source of data was Mother/Father. Predesigned pretested validated structured questionnaire was used to collect the data. Results: Period prevalence of unintentional childhood injury was 18.6%. Fall was reported as most common cause of injury among children. Fall, sharp injuries, burn was associated with certain environmental risk factors. Children were at risk of road traffic injuries, burns, sharp injuries, and fall. Protective factors against injury were children belonging to lower and middle socio-economic status, child with 1 sibling. Conclusions: Period prevalence of unintentional childhood injury was 18.6%. Majority of them had fall as a cause of injury, with the risk factors for fall in the child's environment.